PERBANDINGAN SISTEM DIGESTER ANAEROB TERMOFILIK SATU DAN DUA FASE - Muhammad Abdul Kholiq (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Anaerobic digestion of organic waste has some advantages, namelythe recovery of biogas as alternative energy source and the conversionof waste products to soil fertilizer. Compared to mesophilic digestion,thermophilic digestion offers advantages regarding the processperformance and the hygienic aspect. Unfortunately, the process hasgenerally not enjoyed a good reputation because of its poor record withrespect to process stability. Two-stage anaerobic reactor systemconsisting of a hydrolysis reactor and a methane reactor is often usedto overcome such instability problems. In this study, the two-stageanaerobic reactor system is compared to the one-stage anaerobic reactorsystem. This study shows that the two-stage anaerobic reactor systemhas more process stability, can be operated at much more higher organicloading rate, and need much shorter recovery time after a processfailure.